PENGEMBANGAN MEDIA PROMOSI PERPUSTAKAAN ROSELLA GENEMETRIK - Wulandari, Uci; Hanum, Atiqa Nur Latifa; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The library is not only a place to develop promotional media, but the library also has several activities that exist in libraries in general, such as early childhood education, posyandu and waste banks. The aim of this research is to describe the use of promotional media in the Rosella Genemetric Library and determine the obstacles faced in the use of promotional media. This research uses qualitative methods by collecting data through observation, interviews and documentation. The research subjects were 4 informants. The research results show that the Rosella Genemetry Library has carried out library promotions, but the library is less active and varied in preparing promotional media. The library tries to carry out activities held by the library as a direct approach in promoting its library with the aim of informing about the various collections in the Rosella Genemetri Library so that people are interested in visiting and reading the books there. Therefore, by providing information by promoting the library, we also need to carry out many activities so that other visitors and the public are enthusiastic about participating in each of these activities. With this activity at the Rosella Genemetric library, it can also be used as promotional material for social media such as posting on Instagram, Facebook or other social media when the activity starts.